Overall buckling behaviour of welded π-shaped compression columns. (February 2020) - Chen, Yao; Shu, Ganping; Zheng, Baofeng; Lu, Ruihua
Abstract: The overall buckling behaviour of welded π-shaped columns have been investigated in this study. Twenty-five pin-ended specimens made of Q345 steel with several cross sections and a wide range of lengths were tested under axial compression. The material properties, initial imperfections and longitudinal residual stresses were all examined. The deformed shapes of test specimens involved overall flexural buckling and overall flexural-torsional buckling. The ultimate strengths, deformations and strain distributions of specimens were obtained in the test. The finite element models were established and validated by test results, and then were adopted to carry out a series of parametric studies. The buckling strengths were compared with the design strengths predicted by the current design specifications for steel structures. Reliability analyses were conducted to evaluate the existing design column curves and π-shaped column curve. It is shown that column b-curves in both Eurocode 3 and Chinese standard provide generally conservative predictions for the strengths of π-shaped members, whereas ANSI/AISC specification provides marginally unsafe predictions. A new column curve is proposed and can provide more accurate and reliable predictions for the strengths of welded π-shaped members. Highlights: The failure modes of π-shaped members include flexural buckling and flexural-torsional buckling. Column b-curves in Eurocode and Chinese standard provide conservative strengths of π-shaped members, whereas ANSI/AISC specification provides unsafe predictions. The new column curve can provide more accurate and reliable predictions for the strengths of  π-shaped members.